2015
DOI: 10.1007/s00182-015-0475-9
|View full text |Cite
|
Sign up to set email alerts
|

An equilibrium analysis of the probabilistic serial mechanism

Abstract: Due to copyright restrictions, the access to the full text of this article is only available via subscription.The prominent mechanism of the recent literature in the assignment problem is the probabilistic serial (PS). Under PS, the truthful (preference) proÖle always constitutes an ordinal Nash Equilibrium, inducing a random assignment that satisÖes the appealing ordinal e¢ ciency and envy-freeness properties. We show that both properties may fail to be satisÖed by a random assignment induced in an ordinal Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Somewhat surprisingly, the Nash equilibria of the mechanism were only recently studied. Aziz et al [5] prove that the mechanism has pure Nash equilibria while Ekici and Kesten [14] study the ordinal equilibria of the mechanism and prove that the desirable properties of the mechanism are not necessarily satisfied for those profiles.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Somewhat surprisingly, the Nash equilibria of the mechanism were only recently studied. Aziz et al [5] prove that the mechanism has pure Nash equilibria while Ekici and Kesten [14] study the ordinal equilibria of the mechanism and prove that the desirable properties of the mechanism are not necessarily satisfied for those profiles.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Other interesting aspects of PS and RSD such as computational complexity and best-response strategies have also been explored [8,9,19]. In this vein, Aziz et al proved the existence of pure Nash equilibria, but showed that computing Table 5: A random assignment for a preference profile wherein PS and RSD both prescribe an identical matching, i.e.…”
Section: Related Literaturementioning
confidence: 99%
“…In fact, many mechanisms, such as CEEI, is manipulable as well. Ekici and Kesten (2016) shows that when agents are not truthful, the outcome of Probabilistic Serial may not satisfy desirable properties related to efficiency and envy-freeness. Hence, researchers look to develop refined analytic and experimental works to answer a basic question: which mechanism to employ in practical applications?…”
Section: Introductionmentioning
confidence: 99%